Social Expenditures of Malaysia for the period 2008-2012 - Zulkarnain, H.; Jeevasuthan, S. (OECD/Korea Policy Centre – Health and Social Policy Programme, 2015)
This technical paper on social expenditures was based on the guidelines stipulated by the OECD. The statistics presented are important as they reflect on indicators of social protection programmes and the trend of social expenditures of Malaysia between 2008 and 2012. Six different social protection areas in the country are discussed: Social security, Social Insurance, Social assistance, Subsidies, Healthcare, and Zakat. The focus of the analysis of the above mentioned areas concerns social expenditure levels also expressed as a percentage of Malaysia’s GDP. These details will help to construct an idea of the value of social protection programmes in Malaysia, and facilitate comparison with those of OECD countries and several other South East Asian countries. However, some informal social protection activities such as programmes implemented by the agricultural and fisheries communities were not included as they were not compatible with the OECD guidelines. In conclusion, the paper suggests that the Malaysian government needs to review its present systems and consider what policy changes are necessary to implement better social security protection provisions in each domain, with the final objective of having adequate social expenditure coverage for the nation.